Smart hi-tech ring / Nurul Najwa Ghani, Nabilla Affiqqah Mohd Rosli and Siti Rubaani Sobri - Ghani, Nurul Najwa; Mohd Rosli, Nabilla Affiqqah; Sobri, Siti Rubaani (2017)
The biometric fingerprint is designed for using in systems which acquire fingerprint images from fingerprint readers on client side and send them to a server running Fast Fingerprint Extractor component for further processing. The component is designed to be run on ARM Linux or Android or iOS devices. The technology assures system performance with fast, reliable fingerprint matching in 1-to-1 and 1-to-many modes.